Kerja Sama Indonesia dengan ASEAN Mengenai Cyber Security dan Cyber Resilience dalam Mengatasi Cyber Crime - Kristiani Virgi Kusuma Putri (CV Rewang Rencang, 2021)
Behind the advantages, cyberspace is also has a certain dark side that supports the existence of crimes, such as fraud, terrorist information, pedophilia, and others. In dealing with this, the Indonesian government has made several efforts, one of which is by enacting Law Number 36 of 1999 about Telecommunications and Law Number 11 of 2008 about Information and Electronic Transactions. However, based on research results, from the six ASEAN countries, which are Singapore, Malaysia, Indonesia, Philippines, Thailand, and Vietnam, only Indonesia does not have a specific cybersecurity law. But besides that, in overcoming cybersecurity and resilience, Indonesia is still actively engaged in international cooperation such as joining ASEAN.